IS TRANSLANGUAGING LEGITIMATE IN ENGLISH LEARNING?: STUDENTS’ PERSPECTIVES FROM INDONESIA - Asra, Surya; Rahmiati, Rahmiati; Nucifera, Prima; Fadlia, Fadlia; Mawaddah, Aina (Universitas Islam Sumatera Utara (UISU), 2024)
Translanguaging pedagogy is the balance of using two languages in language learning. As in Indonesian context, the practice of integrating Indonesian language (L1) into English classes (L2) or translanguaging practice is very common to happen. Many students think it is useful for them in learning a foreign language. The students perceived the translingual practice is helpful. However, the teachers still think it is an illegitimate practice. Therefore, this research aims to support the idea of using Indonesian language in English language learning and explore its practice for students scaffolding. The method used was a descriptive qualitative using observations, questionnaires, and interviews. The data source for this research was 40 high school students taught by one English teacher, selected purposefully. The findings of this study show that teachers and students engage in translanguaging activities. The teachers and students use Indonesian language for more than half of the entire teaching and learning process. Although, the teacher still felt that the use of Indonesian language is inevitable due to the students' low abilities. Yet, from the student side, this practice received a positive response. Students found it beneficial for understanding English lessons.